International courts and the performance of international agreements : a general theory with evidence from the European Union - Carrubba, Clifford J.; Gabel, Matthew J. (Cambridge (UK): Cambridge University Press, 2017)
Nations often turn to international courts to help with overcoming collective-action problems associated with international relations. However, these courts generally cannot enforce their rulings, which begs the question: how effective are international courts? This book proposes a general theory of international courts that assumes a court has no direct power over national governments. Member states are free to ignore both the international agreement and the rulings by the court created to enforce that agreement. The theory demonstrates that such a court can, in fact, facilitate cooperation with international law, but only within important political constraints. The authors examine the theoretical argument in the context of the European Union. Using an original data set of rulings by the European Court of Justice, they find that the disposition of court rulings and government compliance with those rulings comport with the theory's predictions.--
1. International courts and compliance -- 2. A theory of courts and compliance in international law -- 3. Putting the theory to the test: evaluating the hypotheses in the European Union -- 4. Preliminary considerations: designing a control for the legal merits -- 5. The political sensitivity hypothesis: third-party briefs and European Court of Justice rulings -- 6. The conditional effectiveness hypothesis: the European Court of Justice and economic integration -- 7. Conclusion.
Includes bibliographical references and index.
Keywords: International courts; International relations; Diplomatic relations; International courts; International relations; European Union countries -- Foreign relations; Europe -- European Union countries